Kebijakan Luar Negeri Indonesia Dalam Pengembangan Pesawat Tempur KF-21 Boramae Dengan Korea Selatan - Rifiza, Muhammad Irfa; Sari, Deasy Silvya; Mubarok, Kiagus Zaenal (Global and Policy Journal of International Relations, 2024)
ABSTRACT One of the reasons for air violations in Indonesia is the lack of its weapon system (alutsista). This study aims to explain Indonesia's foreign policy in the development of the KF-21 Boramae jet fighter with South Korea using the concept of foreign policy. In supporting this research, the author uses a qualitative approach. The data collection techniques used by the researcher in this study are the analysis of archives and documents, as well as internet-based data, such as public documents, newspapers, articles, official reports, and previous research or relevant personal documents. To ensure its validity, the data obtained was processed using data triangulation. The results explain that Indonesia's foreign policy orientation is included in the non-aligned orientation and the orientation of coalition formation and alliance construction. The national role in Indonesia's foreign policy is included in active independent. Indonesia's foreign policy objective is categorized as middle-range. Indonesia's foreign policy action is categorized as a model of reciprocal relations where there is a two-way relationship between two countries that provide mutual benefits. The results of this research contribute to explaining the development of the KF-21 Boramae jet fighter. Keywords: Foreign Policy, Indonesia, KF-21 Boramae, South Korea ABSTRAK Salah satu penyebab pelanggaran udara di Indonesia adalah kurangnya alat sistem persenjataan (alutsista). Penelitian ini bertujuan untuk menjelaskan kebijakan luar negeri Indonesia dalam pengembangan jet tempur KF-21 Boramae dengan Korea Selatan dengan menggunakan konsep kebijakan luar. Dalam mendukung penelitian ini, penulis menggunakan pendekatan kualitatif. Teknik pengumpulan data yang digunakan peneliti dalam penelitian ini adalah analisis terhadap arsip dan dokumen, serta data yang berbasis internet, seperti dokumen publik, surat kabar, artikel, laporan resmi, dan penelitian terdahulu atau dokumen pribadi yang relevan. Untuk menjamin keabsahannya, data yang diperoleh diolah dengan menggunakan triangulasi data. Dari data yang telah diolah, hasil dari penelitian menjelaskan bahwa orientasi kebijakan luar negeri Indonesia termasuk ke dalam orientasi nonblok dan orientasi pembentukan koalisi dan konstruksi aliansi. Peran nasional dalam kebijakan luar negeri Indonesia termasuk dalam active independent. Tujuan kebijakan luar negeri Indonesia termasuk dalam middle-range objective. Aksi kebijakan luar negeri Indonesia dikategorikan sebagai model hubungan timbal balik. Hasil riset ini berkontribusi dalam menjelaskan perkembangan pesawat tempur KF-21 Boramae. Kata Kunci: Kebijakan Luar Negeri, Indonesia, KF-21 Boramae, Korea Selatan